2021
DOI: 10.3390/v13030413
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics Approach for the Improvement of COVID-19 Treatment

Abstract: The treatment of coronavirus disease 2019 (COVID-19) has been a challenge. The efficacy of several drugs has been evaluated and variability in drug response has been observed. Pharmacogenetics could explain this variation and improve patients’ outcomes with this complex disease; nevertheless, several disease-related issues must be carefully reviewed in the pharmacogenetic study of COVID-19 treatment. We aimed to describe the pharmacogenetic variants reported for drugs used for COVID-19 treatment (remdesivir, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 99 publications
0
26
0
1
Order By: Relevance
“…A recent study demonstrated that, like other viral infections, during the progression of COVID-19 local and systemic inflammation as well as the “cytokine storm” will potentially cause downregulation of the major CYP enzymes including CYP3A4 [ 35 ]. A new study proposed that COVID-19 pharmacogenetic studies include CYP3A4 variants [ 36 ]. The [ 33 ] study shows that CYPs metabolic activity will be surely changed during the SARS-CoV-2 infection in a similar manner, resulting in a pharmacokinetic interaction with the recommended drugs for COVID-19 treatments.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study demonstrated that, like other viral infections, during the progression of COVID-19 local and systemic inflammation as well as the “cytokine storm” will potentially cause downregulation of the major CYP enzymes including CYP3A4 [ 35 ]. A new study proposed that COVID-19 pharmacogenetic studies include CYP3A4 variants [ 36 ]. The [ 33 ] study shows that CYPs metabolic activity will be surely changed during the SARS-CoV-2 infection in a similar manner, resulting in a pharmacokinetic interaction with the recommended drugs for COVID-19 treatments.…”
Section: Resultsmentioning
confidence: 99%
“…Ivermectin is also a substrate of P-gp encoded by the ABCB1, and genetic polymorphisms of ABCB1 have linked to severe neurologic ADRs (Lespine et al, 2006;Baudou et al, 2020). Also, ivermectin is transported by the OATP1A2 and OATP2B1 encoded by the SLCO1A2 and SLCO2B1, respectively, although no pharmacogenetic study was identified for this association to date in the literature (Fricke-Galindo and Falfán-Valencia, 2021;Telbisz et al, 2021).…”
Section: Ivermectinmentioning
confidence: 99%
“…The SNP rs71647871 of CES1 has been found to be associated with variation in plasma concentration-time curve of oseltamivir (Tarkiainen et al, 2012) The PK of oseltamivir may also be affected by the ABCB1, CES1, NEU2, and SLC15A1 genetic variants. The SNP rs1045642 of ABCB1 was associated with neurologic ADRs developed by oseltamivir (Bermúdez de León et al, 2020;Fricke-Galindo and Falfán-Valencia, 2021).…”
Section: Oseltamivirmentioning
confidence: 99%
“…In another study, the variability in drug responses in COVID-19 patients was evaluated based on pharmacogenetics as a means of improving patient outcomes [ 21 ]. The pharmacogenetics for the treatment of COVID-19 with remdesivir, oseltamivir, lopinavir, ritonavir, azithromycin, chloroquine, HCQ, ivermectin, and dexamethasone was investigated.…”
Section: Clinical Findingsmentioning
confidence: 99%